Effect of Annealing on the Band Alignment of ALD SiO2 on (AlxGa1-x)2O3 for x = 0.2 - 0.65. (1st January 2019) - Fares, Chaker; Islam, Zahabul; Haque, Aman; Kneiß, Max; von Wenckstern, Holger; Grundmann, Marius; Tadjer, Marko; Ren, Fan; Pearton, S. J.
Abstract : Heterostructures of Atomic Layer Deposited SiO2 on thin layers of (Alx Ga1-x )2 O3  with x = 0.2 - 0.65 deposited by Pulsed Laser Deposition were annealed at 600°C to simulate ohmic contact formation in MOS devices. The valence band offsets decrease significantly as a result of this annealing, with the change dependent on the initial Al composition. The decrease ranges from 0.65 eV for (Al0.20 Ga0.80 )2 O3 to 1.75 eV for (Al0.65 Ga0.35 )2 O3 and is likely due to an increase in interfacial disorder as a result of annealing. Concurrently, the conduction band offsets increase, improving carrier confinement for electrons within the heterostructure. The band alignment remains type I (nested gap) across the entire composition range examined.